Platelet-derived growth factor-beta receptor activation is essential for fibroblast and pericyte recruitment during cutaneous wound healing. - Rajkumar, V; Shiwen, X; Bostrom, M; Leoni, P; Muddle, J; Ivarsson, M; Gerdin, B; Denton, C; Bou-Gharios, G; Black, C; Abraham, D (2006)
Connective tissue remodeling provides mammals with a rapid mechanism to repair wounds after injury. Inappropriate activation of this reparative process leads to scarring and fibrosis. Here, we studied the effects of platelet-derived growth factor receptor-beta blockade in vivo using the platelet-derived growth factor receptor (PDGFR)-beta inhibitor imatinib mesylate on tissue repair. After 7 days, healing of wounds was delayed with significantly reduced wound closure and concomitant reduction in myofibroblast frequency, expression of fibronectin ED-A, and collagen type I. Using a collagen type I transgenic reporter mouse, we showed that inhibiting PDGFR-beta activation restricted the distribution of collagen-synthesizing cells to wound margins and dramatically reduced cell proliferation in vivo. By 14 days, treated wounds were fully closed. Blocking PDGFR-beta signaling did not prevent the differentiation of myofibroblasts in vitro but potently inhibited fibroblast proliferation and migration. In addition, PDGFR-beta inhibition in vivo was accompanied by abnormal microvascular morphogenesis reminiscent of that observed in PDGFR-beta-/- mice with significantly reduced immunostaining of the pericyte marker NG2. Imatinib treatment also inhibited pericyte proliferation and migration in vitro. This study highlights the significance of PDGFR-beta signaling for the recruitment, proliferation, and functional activities of fibro-blasts and pericytes during the early phases of wound healing.